Immunomodulatory potential of flavonoids for the treatment of autoimmune diseases and tumour. (2nd November 2021) - Han, Limin; Fu, Qiang; Deng, Chuan; Luo, Li; Xiang, Tengxiao; Zhao, Hailong
Abstract: The immune system plays an indispensable role in maintaining human health against the invasion of foreign materials, microorgainisms and pathogens. The autoimmune diseases and chronic inflammatory disorders are characterized by dysregulated immune responses resulting in excessive and uncontrolled tissue inflammation, as well as tumour, and others. In recent years, flavonoids are widely recognized as potentially natural polyphenol compounds for the treatment of multiple diseases, given their immunomodulatory activity, antioxidant and antineoplastic activities. However, the exact mechanisms of flavonoids on the immune system and inhibiting tumour remains unclear. This review article provides an overview of the impact and mechanism of flavonoids on innate and adaptive immune system through the analysis of various immune cells. Meanwhile, we also explain the probable therapeutic mechanism of flavonoids on tumour and other chronic diseases. Overall, this review may provide a certain theoretical direction and theoretical basis for the application of flavonoids in the treatment of immune‐related disorders and tumour.